Evidence Based Surgical Approach to Locally Advanced Gastric Cancer - Thakur, Binay; Devkota, Mukti; Sharma, Amit; Chaudhary, Manish (Journal of Nepal Health Research Council, 2019)
Gastric cancer is endemic in China, Japan, Korea, Brazil and Former Soviet Union. Patients are diagnosed usually in locally advanced stage. Endoscopy, Positron Emission Therapy- Computed Tomography, Endoscopic ultrasound and staging laparoscopy are the tools for proper evaluation of such patients. Locally advanced gastric cancer (T2-4N0 or TanyN+) requires multimodality treatment including surgery. Resection is the cornerstone of cure for gastric adenocarcinoma; however, several aspects of surgical intervention remain controversial or are suboptimally applied at a population level. Current evidence shows a D2 gastrectomy has got the best survival results. At least 15 lymph nodes should be assessed for adequate staging. Laparoscopic resections should be performed to the same standards as those for for open resections, by surgeons who are experienced in both advanced laparoscopic surgery and gastric cancer management. Keywords: Curative surgery; gastrectomy; stomach neoplasms.